A method for producing a wear-resistant gradient material for elevator safety gear shoes

CN118635523BActive Publication Date: 2026-10-23XIAN SPECIAL EQUIP INSPECTION INST +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410694327.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2026-10-23
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

同步送粉法中,常见的为单路同步同轴送粉,其可以容易地成形所设计零部件的三维形貌,但是无法实现在激光立体成形过程中对材料的种类或成分进行实时调控,因而在梯度材料的激光立体成形就存在较大缺陷,更谈不上成形一些复杂的复合梯度材料

Benefits of technology

[0021]1、本发明提供一种制备电梯安全钳楔块耐磨梯度材料的方法,该方法创造性地引入多路同步旁轴送粉激光立体成形技术制备得到电梯安全钳楔块耐磨梯度材料,以钴基合金和含有钴基合金、碳化硅陶瓷粉末和碳化硼陶瓷粉末的混合粉料为主要原料,获得无界面梯度分布、具有良好的耐蚀性、高比模量、高比强度和高耐磨性,同时在高温环境下能表现出良好的性能,符合安全钳楔块的性能需求的电梯安全钳楔块。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118635523B_ABST
    Figure CN118635523B_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing elevator safety gear wedge wear-resistant gradient material, comprising the following steps: synchronously feeding two paths of powder to the position of laser beam spot by adopting multi-path synchronous off-axis powder feeding mode, and making the powder melt and deposit into shape; one path of the two paths of powder is cobalt-based alloy powder, and the other path of the two paths of powder is mixed powder containing cobalt-based alloy powder, silicon carbide ceramic powder and boron carbide ceramic powder. The elevator safety gear wedge wear-resistant gradient material is prepared by creatively introducing multi-path synchronous off-axis powder feeding laser stereolithography technology, and the elevator safety gear wedge wear-resistant gradient material is obtained by taking cobalt-based alloy and mixed powder containing cobalt-based alloy, silicon carbide ceramic powder and boron carbide ceramic powder as main raw materials. The obtained elevator safety gear wedge wear-resistant gradient material has no interface gradient distribution, good corrosion resistance, high specific modulus, high specific strength and high wear resistance, and can exhibit good performance of the wedge under high-temperature environment, and meets the performance requirement of the safety gear wedge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials forming technology, specifically relating to a method for preparing a wear-resistant gradient material for elevator safety clamp wedges. Background Technology

[0002] An elevator mainly consists of two parts: the mechanical system and the electrical control system. The mechanical system includes the traction system, guiding system, car system, door system, and gravity balancing system; the electrical system includes the electric drive system, electrical control system, and safety protection system. The speed governor, linkage mechanism, and safety brake device in the elevator safety protection system constitute the elevator's braking system. When the elevator experiences dangerous situations such as a broken wire rope, car overspeeding, or accidental fall, the speed governor activates, clamping the wire rope. Through friction in the sheaves, the linkage mechanism triggers the safety brake, causing the wedges on both sides of the safety brake to lift synchronously and contact the guide rails, achieving self-locking and stopping. The elevator safety brake braking principle utilizes the friction work at the interface between the guide rails and wedges to dissipate the system's mechanical energy and achieve car braking. Most of the friction work during braking is converted into frictional heat, which is transferred to the guide rails and wedges via heat conduction and dissipated to the surrounding air through heat convection on the outer surface. Frictional heat generation leads to temperature rise in the guide rail and wedge. Different heat dissipation conditions in the wedge friction pair areas create an uneven temperature field, resulting in severe thermal deformation and stress in high-temperature regions. Increased contact pressure in severely deformed, high-temperature areas further increases frictional heat and temperature, exacerbating the thermal deformation of the wedge and guide rail. During friction braking, the thermal deformation of the contact materials affects the distribution of contact pressure, which in turn determines the distribution of frictional heat, thus influencing the temperature field distribution. Therefore, the friction braking process of the safety clamp is a typical thermomechanical coupling process. Furthermore, frictional temperature rise affects the wear and frictional behavior of the braking material surface. As a key component of the elevator braking system, the material properties of the safety clamp wedge have a significant impact on elevator braking performance.

[0003] In typical composite materials, the dispersed phase is uniformly distributed, resulting in consistent overall material properties. However, in certain situations, it is desirable for the two sides of the same material to possess different properties or functions, while simultaneously achieving a perfect bond between the two sides of different materials. This prevents material failure due to performance mismatches under demanding operating conditions. In recent years, functionally graded materials have seen rapid development. For example, the hypersonic combustion ramjet engine, a prime example in the space shuttle propulsion system, continuously alters the composition and structure of two materials to eliminate their internal interfaces, thereby obtaining a heterogeneous material whose function gradually changes according to the composition and structure.

[0004] Laser stereolithography is an important surface modification technology. Developed based on rapid prototyping, it's an advanced manufacturing technology capable of achieving near-net-shape forming of dense metal parts and has begun to be applied in the aerospace field. Laser stereolithography primarily uses a laser beam to irradiate powder, causing it to melt, deposit, and solidify. The powder feeding processes are mainly divided into two categories: powder pre-placement and synchronous powder feeding. Compared to powder pre-placement, synchronous powder feeding laser stereolithography requires the interaction of the laser beam, substrate, and powder alloy particles to achieve layer-by-layer stacking, thereby preparing the desired material. Materials prepared using this powder feeding process have the characteristics of high coating quality, minimal deformation under high temperatures, and dense microstructure in the cladding zone. In synchronous powder feeding, single-path synchronous coaxial powder feeding is common. While it can easily form the three-dimensional morphology of the designed parts, it cannot achieve real-time control of the material type or composition during the laser stereolithography process. Therefore, it has significant limitations in the laser stereolithography of gradient materials, let alone the formation of complex composite gradient materials. Summary of the Invention

[0005] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing a method for preparing wear-resistant gradient materials for elevator safety clamp wedges. This invention creatively introduces multi-channel synchronous off-axis powder feeding laser stereolithography technology to prepare wear-resistant gradient materials for elevator safety clamp wedges. Using cobalt-based alloys and mixed powders containing cobalt-based alloys, silicon carbide ceramic powder, and boron carbide ceramic powder as main raw materials, the resulting elevator safety clamp wedge wear-resistant gradient material exhibits a non-interfacial gradient distribution, good corrosion resistance, high specific modulus, high specific strength, and high wear resistance. It also demonstrates good performance under high-temperature environments, meeting the performance requirements of safety clamp wedges.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing wear-resistant gradient material for elevator safety clamp wedges, wherein the wear-resistant gradient material for elevator safety clamp wedges is prepared by laser stereolithography, characterized in that it includes: simultaneously feeding two powders to the laser beam spot position using a multi-channel synchronous off-axis powder feeding method, so that the powders melt and deposit to form a shape; one of the two powders is cobalt-based alloy powder, and the other is a mixed powder containing cobalt-based alloy powder, silicon carbide ceramic powder and boron carbide ceramic powder.

[0007] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized by specifically including the following steps:

[0008] Step 1: Pre-treat cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder separately;

[0009] Step 2: According to the preset ratio of the mixed powder, mix the pretreated cobalt-based alloy powder, pretreated silicon carbide ceramic powder and pretreated boron carbide ceramic powder in a ball mill to obtain the mixed powder.

[0010] Step 3: Preheat the cobalt-based alloy powder pretreated in Step 1 and the mixed powder from Step 2 separately;

[0011] Step 4: Start the laser stereolithography equipment, using argon as the protective gas, and prepare the wear-resistant gradient material on the substrate by multi-channel synchronous off-axis powder feeding and laser cladding, using the preheated cobalt-based alloy powder and the preheated mixed powder from Step 3.

[0012] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that, in step one, the pretreatment specifically includes: placing the cobalt-based alloy powder, silicon carbide ceramic powder and boron carbide ceramic powder in a high-temperature furnace at 120°C and drying them for 2 hours.

[0013] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that, in step one, the cobalt-based alloy powder is spherical Stellite alloy powder with an average particle size <60μm, and is prepared by mixing the following raw materials in weight percentage: C 2.4%, Cr 30.5%, Si 1.0%, W 12.5%, Fe 3.0%, Mo 1.0%, Ni 3.0%, Mn 0.25%, and Co balance; the silicon carbide ceramic powder has a SiC content >99% by weight and an average particle size <10μm; the boron carbide ceramic powder has a BC content >99% by weight and an average particle size <15μm.

[0014] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that, in step two, the preset proportions, by mass, are: 94-96% cobalt-based alloy, 2-3% silicon carbide ceramic, and 2-3% boron carbide ceramic.

[0015] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that, in step three, the preheating specifically includes: placing the cobalt-based alloy powder pretreated in step one and the mixed powder in step two into an oven at 120°C for 2 hours.

[0016] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that, in step four, the preparation of the wear-resistant gradient material specifically includes: loading preheated cobalt-based alloy powder and preheated mixed powder into the multi-channel synchronous off-axis powder feeding system of a laser stereolithography equipment, preheating the substrate, adjusting the first nozzle, the second nozzle and the laser beam to face the substrate, spraying the preheated cobalt-based alloy powder from the first nozzle according to a preset powder feeding amount, spraying the preheated mixed powder from the second nozzle according to a preset powder feeding amount, and scanning synchronously with the laser beam to form a spot on the substrate to melt the sprayed cobalt-based alloy powder and mixed powder, thereby depositing and forming the material.

[0017] The method for preparing wear-resistant gradient material for elevator safety clamp wedges, as described above, is characterized by the following: the substrate preheating temperature is 1600–1800℃, the preheating time is 1–2 h, the powder feeding pressure is 0.7–0.8 MPa, the powder feeding voltage is 20–24 V, the scanning speed is 800–1200 mm / h, the protective atmosphere argon gas pressure is 0.06–0.08 MPa, the laser power is 1400–1600 W, and the spot diameter is 2 mm.

[0018] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that the thickness of the wear-resistant gradient material is 50-60 mm.

[0019] The above-mentioned method for preparing wear-resistant gradient material for elevator safety clamp wedges is characterized in that, after preheating, the preset powder feeding amount of cobalt-based alloy powder decreases uniformly from 0 min to (220 to 240) min, and the powder feeding amount decreases uniformly from 6 to 10 g / min to 0 g / min; after preheating, the preset powder feeding amount of mixed powder increases uniformly from 0 min to (220 to 240) min, and the powder feeding amount increases uniformly from 0 g / min to 6 to 10 g / min; and the total powder feeding amount of cobalt-based alloy powder and mixed powder after preheating is maintained at 6 to 10 g / min.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] 1. This invention provides a method for preparing wear-resistant gradient materials for elevator safety clamp wedges. This method creatively introduces multi-channel synchronous off-axis powder feeding laser stereolithography technology to prepare wear-resistant gradient materials for elevator safety clamp wedges. The main raw materials are cobalt-based alloys and mixed powders containing cobalt-based alloys, silicon carbide ceramic powders and boron carbide ceramic powders. This results in elevator safety clamp wedges with interface-free gradient distribution, good corrosion resistance, high specific modulus, high specific strength and high wear resistance, and good performance under high temperature environment, meeting the performance requirements of safety clamp wedges.

[0022] 2. The method for preparing wear-resistant gradient material for elevator safety clamp wedges in this invention includes using cobalt-based alloys as the main raw material, which can make full use of its high microhardness, good wear resistance, low oxide content, high coating bonding strength and other performance characteristics.

[0023] 3. The method for preparing wear-resistant gradient material for elevator safety clamp wedges of the present invention includes feeding cobalt-based alloy powder and mixed powder into a substrate through two nozzles according to a preset powder feeding amount for melting. During the powder feeding process, the powder feeding amount of cobalt-based alloy powder and mixed powder is kept constant, which can effectively maintain the continuous change of material composition and eliminate the interface effect.

[0024] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0025] Instruction manual illustrations

[0026] Figure 1 The image shows a metallographic photograph of the wear-resistant gradient material of the elevator safety clamp wedge block in Example 1. Detailed Implementation

[0027] Example 1

[0028] This embodiment provides a method for preparing wear-resistant gradient material for elevator safety clamp wedges, including the following steps:

[0029] Step 1: Pre-treat cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder separately, specifically including: drying the cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder in a high-temperature furnace at 120°C for 2 hours respectively; the cobalt-based alloy is a spherical Stellite alloy powder with an average particle size <60μm, and is made by mixing raw materials in the following weight percentages: C 2.4%, Cr 30.5%, Si 1.0%, W 12.5%, Fe 3.0%, Mo 1.0%, Ni 3.0%, Mn 0.25%, and Co balance; the silicon carbide ceramic powder has a SiC content >99% by weight and an average particle size <10μm; the boron carbide ceramic powder has a BC content >99% by weight and an average particle size <15μm.

[0030] Step 2: According to the preset ratio of the mixed powder, the pretreated cobalt-based alloy powder, pretreated silicon carbide ceramic powder, and pretreated boron carbide ceramic powder from Step 1 are mixed evenly in a ball mill to obtain a cobalt-based alloy / SiC ceramic / BC ceramic mixed powder; the preset ratio, by mass, is: 94% cobalt-based alloy, 3% silicon carbide ceramic, and 3% boron carbide ceramic.

[0031] Step 3: Place the pretreated cobalt-based alloy powder from Step 1 and the mixed powder from Step 2 into an oven at 120℃ and bake for 2 hours; this can effectively improve the flowability of the powder.

[0032] Step 4: Start the laser stereolithography equipment, using argon as the protective gas. Through multi-channel synchronous off-axis powder feeding and laser cladding, prepare a wear-resistant gradient material on the substrate by preheating the cobalt-based alloy powder and the preheated mixed powder in Step 3. Specifically, this includes: loading the preheated cobalt-based alloy powder and the preheated mixed powder into the multi-channel synchronous off-axis powder feeding system of the laser stereolithography equipment, preheating the substrate, adjusting the first nozzle, the second nozzle, and the laser beam to face the substrate, ejecting the preheated cobalt-based alloy powder from the first nozzle according to the preset powder feeding amount, and ejecting the preheated mixed powder from the second nozzle according to the preset powder feeding amount. The laser beam scans synchronously, forming a spot on the substrate to melt the ejected cobalt-based alloy powder and mixed powder, thus depositing and forming the material. The substrate preheating temperature is 1600℃, the preheating time is 1 hour, and the powder feeding pressure is 0. The laser pressure was 7 MPa, the powder feeding voltage was 20 V, the scanning speed was 800 mm / h, the protective atmosphere argon pressure was 0.06 MPa, the laser power was 1400 W, and the spot diameter was 2 mm; the thickness of the wear-resistant gradient material was 60 mm; the laser stereolithography equipment was a BLT-400 laser melting and forming equipment, purchased from Xi'an Bright Laser Technologies Co., Ltd.; after preheating, the preset powder feeding amount of the cobalt-based alloy powder decreased uniformly from 0 min to 240 min, and the powder feeding amount decreased uniformly from 6 g / min to 0 g / min; after preheating, the preset powder feeding amount of the mixed powder increased uniformly from 0 min to 240 min, and the powder feeding amount increased uniformly from 0 g / min to 6 g / min; the total powder feeding amount of the cobalt-based alloy powder and the mixed powder after preheating remained at 6 g / min.

[0033] Figure 1 The image shows a metallographic photograph of the wear-resistant gradient material of the elevator safety clamp wedge block in Example 1. It can be clearly observed from the image that the gradient material has a uniform microstructure and a dense structure, with a uniform increase in SiC ceramic and BC ceramic reinforcing phases, and the gradient material has no obvious interface.

[0034] Example 2

[0035] This embodiment provides a method for preparing wear-resistant gradient material for elevator safety clamp wedges, including the following steps:

[0036] Step 1: Pre-treat cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder separately, specifically including: drying the cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder in a high-temperature furnace at 120°C for 2 hours respectively; the cobalt-based alloy is a spherical Stellite alloy powder with an average particle size <60μm, and is made by mixing raw materials in the following weight percentages: C 2.4%, Cr 30.5%, Si 1.0%, W 12.5%, Fe 3.0%, Mo 1.0%, Ni 3.0%, Mn 0.25%, and Co balance; the silicon carbide ceramic powder has a SiC content >99% by weight and an average particle size <10μm; the boron carbide ceramic powder has a BC content >99% by weight and an average particle size <15μm.

[0037] Step 2: According to the preset ratio of the mixed powder, the cobalt-based alloy powder, the pretreated silicon carbide ceramic powder, and the pretreated boron carbide ceramic powder from Step 1 are mixed evenly in a ball mill to obtain a cobalt-based alloy / SiC ceramic / BC ceramic mixed powder; the preset ratio, by mass, is: 95% cobalt-based alloy, 2.5% silicon carbide ceramic, and 2.5% boron carbide ceramic.

[0038] Step 3: Place the pretreated cobalt-based alloy powder from Step 1 and the mixed powder from Step 2 into an oven at 120℃ and bake for 2 hours.

[0039] Step 4: Start the laser stereolithography equipment, using argon as the protective gas. Through multi-channel synchronous off-axis powder feeding and laser cladding, prepare a wear-resistant gradient material on the substrate by depositing the preheated cobalt-based alloy powder and preheated mixed powder from Step 3 onto the substrate. Specifically, this includes: loading the preheated cobalt-based alloy powder and preheated mixed powder into the multi-channel synchronous off-axis powder feeding system of the laser stereolithography equipment to preheat the substrate; adjusting the first nozzle, second nozzle, and laser beam to face the substrate; ejecting the preheated cobalt-based alloy powder from the first nozzle according to the preset powder feeding amount; ejecting the preheated mixed powder from the second nozzle according to the preset powder feeding amount; and synchronously scanning the laser beam to form a spot on the substrate to melt the ejected cobalt-based alloy powder and mixed powder, thus depositing and forming the material. The substrate preheating temperature is [temperature missing]. The temperature was 1700℃, the preheating time was 1.5h, the powder feeding pressure was 0.75MPa, the powder feeding voltage was 22V, the scanning speed was 1000mm / h, the protective atmosphere argon pressure was 0.07MPa, the laser power was 1500W, and the spot diameter was 2mm; the thickness of the wear-resistant gradient material was 55mm; after preheating, the preset powder feeding amount of the cobalt-based alloy powder decreased uniformly from 8g / min to 0g / min from 0min to 230min, and the preset powder feeding amount of the preheated mixed powder increased uniformly from 0g / min to 8g / min from 0min to 230min, and the total powder feeding amount of the preheated cobalt-based alloy powder and the preheated mixed powder remained at 8g / min.

[0040] The performance of the wear-resistant gradient composite material for the elevator safety clamp wedge in this embodiment is basically the same as that in Embodiment 1, exhibiting extremely high resistance to friction and wear and impact resistance, which can meet the requirements of the working environment of the elevator safety clamp wedge material.

[0041] Example 3

[0042] This embodiment provides a method for preparing wear-resistant gradient material for elevator safety clamp wedges, including the following steps:

[0043] Step 1: Pre-treat cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder separately, specifically including: drying the cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder in a high-temperature furnace at 120°C for 2 hours respectively; the cobalt-based alloy is a spherical Stellite alloy powder with an average particle size <60μm, and is made by mixing raw materials in the following weight percentages: C 2.4%, Cr 30.5%, Si 1.0%, W 12.5%, Fe 3.0%, Mo 1.0%, Ni 3.0%, Mn 0.25%, and Co balance; the silicon carbide ceramic powder has a SiC content >99% by weight and an average particle size <10μm; the boron carbide ceramic powder has a BC content >99% by weight and an average particle size <15μm.

[0044] Step 2: According to the preset ratio of the mixed powder, the pretreated cobalt-based alloy powder, pretreated silicon carbide ceramic powder, and pretreated boron carbide ceramic powder from Step 1 are mixed evenly in a ball mill to obtain a cobalt-based alloy / SiC ceramic / BC ceramic mixed powder; the preset ratio, by mass, is: 96% cobalt-based alloy, 2% silicon carbide ceramic, and 2% boron carbide ceramic.

[0045] Step 3: Place the pretreated cobalt-based alloy powder from Step 1 and the mixed powder from Step 2 into an oven at 120℃ and bake for 2 hours.

[0046] Step 4: Start the laser stereolithography equipment, using argon as the protective gas. Through multi-channel synchronous off-axis powder feeding and laser cladding, prepare a wear-resistant gradient material on the substrate by depositing the preheated cobalt-based alloy powder and preheated mixed powder from Step 3 onto the substrate. Specifically, this includes: loading the preheated cobalt-based alloy powder and preheated mixed powder into the multi-channel synchronous off-axis powder feeding system of the laser stereolithography equipment to preheat the substrate; adjusting the first nozzle, second nozzle, and laser beam to face the substrate; ejecting the preheated cobalt-based alloy powder from the first nozzle according to the preset powder feeding amount; ejecting the preheated mixed powder from the second nozzle according to the preset powder feeding amount; and synchronously scanning the laser beam to form a spot on the substrate to melt the ejected cobalt-based alloy powder and mixed powder, thus depositing and forming the material. The substrate preheating temperature is [temperature missing]. The temperature was 1800℃, the preheating time was 2h, the powder feeding pressure was 0.8MPa, the powder feeding voltage was 24V, the scanning speed was 1200mm / h, the protective atmosphere argon pressure was 0.08MPa, the laser power was 1600W, and the spot diameter was 2mm; the thickness of the wear-resistant gradient material was 50mm; after preheating, the preset powder feeding amount of the cobalt-based alloy powder decreased uniformly from 0min to 220min, and the powder feeding amount decreased uniformly from 10g / min to 0g / min; after preheating, the preset powder feeding amount of the mixed powder increased uniformly from 0min to 220min, and the powder feeding amount increased uniformly from 0g / min to 10g / min; the total powder feeding amount of the cobalt-based alloy powder and the mixed powder after preheating was kept at 10g / min.

[0047] The performance of the wear-resistant gradient composite material for the elevator safety clamp wedge in this embodiment is basically the same as that in Embodiment 1, exhibiting extremely high resistance to friction and wear and impact resistance, which can meet the requirements of the working environment of the elevator safety clamp wedge material.

[0048] Performance Evaluation

[0049] The wear-resistant gradient materials for elevator safety clamp wedges in Examples 1-3 were subjected to friction and wear tests using a friction and wear testing machine. A load of 200 N was applied at a rotation speed of 2000 r / min. The test method was based on GB-T12444-2006, "Metallic Materials Wear Test Method". The wear amounts after 30 h, 60 h, and 90 h of wear are shown in Table 1. From the test data in Table 1, it can be observed that under the same friction and wear test conditions, the wear amount of the wear-resistant gradient material for elevator safety clamp wedges of the present invention is much smaller than that of traditional elevator safety clamps. This indicates that the wear-resistant gradient material for elevator safety clamp wedges of the present invention has excellent wear resistance and fully meets the requirements of the working environment of elevator safety clamps.

[0050] Table 1. Wear resistance properties of the wear-resistant gradient material for the elevator safety clamp wedge block of the present invention.

[0051]

[0052] The conventional elevator safety clamp is made of 45 steel.

[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, alterations, and equivalent structural changes made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant gradient material for elevator safety clamp wedges, wherein the wear-resistant gradient material for elevator safety clamp wedges is prepared by laser stereolithography, characterized in that, include: Two powder particles are simultaneously fed to the laser beam spot using a multi-channel synchronous off-axis powder feeding method, causing the powder to melt and deposit into shape. One powder particle is a cobalt-based alloy powder, and the other is a mixed powder containing cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder. The specific steps include: Step 1: Pre-treat cobalt-based alloy powder, silicon carbide ceramic powder, and boron carbide ceramic powder separately; the cobalt-based alloy powder is spherical Stellite alloy powder with an average particle size <60μm, and is prepared by mixing raw materials in the following weight percentages: C 2.4%, Cr 30.5%, Si 1.0%, W 12.5%, Fe 3.0%, Mo 1.0%, Ni 3.0%, Mn 0.25%, and Co balance; the silicon carbide ceramic powder has a SiC content >99% by weight and an average particle size <10μm; the boron carbide ceramic powder has a BC content >99% by weight and an average particle size <15μm. Step 2: According to the preset ratio of the mixed powder, the pretreated cobalt-based alloy powder, the pretreated silicon carbide ceramic powder, and the pretreated boron carbide ceramic powder from Step 1 are mixed evenly in a ball mill to obtain a mixed powder; the preset ratio, by mass, is: 94-96% cobalt-based alloy, 2-3% silicon carbide ceramic, and 2-3% boron carbide ceramic. Step 3: Preheat the cobalt-based alloy powder pretreated in Step 1 and the mixed powder from Step 2 separately; Step 4: Start the laser stereolithography equipment, using argon as the protective gas. Through multi-channel synchronous off-axis powder feeding and laser cladding, prepare a wear-resistant gradient material on the substrate by applying the preheated cobalt-based alloy powder and preheated mixed powder from Step 3. Specifically, this includes: loading the preheated cobalt-based alloy powder and preheated mixed powder into the multi-channel synchronous off-axis powder feeding system of the laser stereolithography equipment; preheating the substrate; adjusting the first nozzle, second nozzle, and laser beam to face the substrate; ejecting the preheated cobalt-based alloy powder from the first nozzle according to the preset powder feeding amount; ejecting the preheated mixed powder from the second nozzle according to the preset powder feeding amount; and synchronously scanning with the laser beam. A light spot is formed on the substrate to melt and spray cobalt-based alloy powder and mixed powder, thus depositing and shaping them. After preheating, the preset powder feeding rate of the cobalt-based alloy powder decreases uniformly from 6-10 g / min to 0 g / min from the start to the end of printing. After preheating, the preset powder feeding rate of the mixed powder increases uniformly from 0 g / min to 6-10 g / min from the start to the end of printing. The total powder feeding rate of the cobalt-based alloy powder and the mixed powder after preheating is always maintained at 6-10 g / min. The total printing time is 220-240 min.

2. The method for preparing wear-resistant gradient material for elevator safety clamp wedges according to claim 1, characterized in that, In step one, the pretreatment specifically includes: placing the cobalt-based alloy powder, silicon carbide ceramic powder and boron carbide ceramic powder in a high-temperature furnace at 120°C and drying them for 2 hours.

3. The method for preparing wear-resistant gradient material for elevator safety clamp wedges according to claim 1, characterized in that, In step three, the preheating specifically includes: placing the cobalt-based alloy powder pretreated in step one and the mixed powder from step two into an oven at 120°C and baking for 2 hours.

4. The method for preparing wear-resistant gradient material for elevator safety clamp wedges according to claim 1, characterized in that, The substrate preheating temperature is 1600-1800℃, the preheating time is 1-2h, the powder feeding pressure is 0.7-0.8MPa, the powder feeding voltage is 20-24V, the scanning speed is 800-1200mm / h, the protective atmosphere argon gas pressure is 0.06-0.08MPa, the laser power is 1400-1600W, and the spot diameter is 2mm.

5. The method for preparing wear-resistant gradient material for elevator safety clamp wedges according to claim 1, characterized in that, The thickness of the wear-resistant gradient material is 50-60 mm.

Citation Information

Patent Citations

  • Preparation method of wear-resistant coating of high-speed elevator safety tongs

    CN112251708A

  • Powder feeding device and laser cladding additive manufacturing system and method with powder feeding device

    CN113182534A

  • Additive preparation method for gradient composite coating on surface of heat distribution pipeline

    CN117020225A